Failure analysis of GFRP single lap joints tailored with a combination of tough epoxy and hyperelastic adhesives - Srinivasan, Dharun Vadugappatty (2020)
Fibre reinforced polymeric composites bonded with epoxy adhesives often fail ungraciously, manifesting fibre-tear failure due to the edge peel stresses. This research work proposes phenol formaldehyde-based hyperelastic adhesive (AF32), as a compliant adhesive for tailoring the single lap joints consisting of GFRP adherends and well-toughened epoxy adhesive (AF3109 and EA9696) joints. The failure strength of the AF3109 and EA9696 adhesive joints is increased by 51.64% and 24.25%, respectively by having 20% volume of compliant adhesive in the bond line. Finite element simulations with Exponential Drucker-Prager (EDP) and Marlow strain energy models are carried out to simulate the experimental load-displacement response. Different failure mechanisms and the influence of adhesive intermingling are revealed by the failure analysis. Finally, a failure mode map for the tailored adhesive joints is proposed in terms of normalised strength ratio and the normalised volume of the compliant adhesive.